Focused Fluid Flow, Shallow Gas Hydrate, and Cold Seep in the Qiongdongnan Basin, Northwestern South China Sea. (12th June 2021) - Geng, Minghui; Zhang, Ruwei; Yang, Shengxiong; Guo, Jun; Chen, Zongheng
Abstract : The 3D seismic data acquired in the central Qiongdongnan Basin, northwestern South China Sea, reveal the presence of shallow gas hydrate, free gas, and focused fluid flow in the study area, which are indicated by multiple seismic anomalies, including bottom simulating reflectors, polarity reverses, pulldowns, minor faults, and gas chimneys intensively emplaced within the shallow strata. A new cold seep is also discovered at approximately 1520 m water depths with an ~40 m wide crater in the west part of the study area. Water column imaging, seafloor observation, and sampling using the remotely operated vehicle "Haima" demonstrate ongoing gas seepages and shallow gas hydrates at this site. Thermogenic gas in the study area migrates from the deep reservoir through the gas hydrate stability zone along deep faults and gas chimneys, forms shallow gas hydrate and free gas, and sustains localized gas seepage within this cold seep. The results provide insight into the relationship between shallow gas hydrate accumulation and deep hydrocarbon generation and migration and simultaneously have important implications for hydrocarbon explorations in the Qiongdongnan Basin, northwestern South China Sea.